2007
DOI: 10.1111/j.1525-1438.2006.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of developing ovarian cancer among women with ovarian endometrioma: a cohort study in Shizuoka, Japan

Abstract: Although some studies have indicated that endometriosis may increase the risk of developing ovarian cancer, there are no data from epidemiologic studies in Japan. We prospectively analyzed all cases of ovarian endometrioma enrolled in the prefecture-wide Shizuoka Cohort Study on Endometriosis and Ovarian Cancer Programme, which was initiated in 1985. To evaluate the risk of ovarian cancer by time periods subsequent to ovarian endometrioma diagnosis, a cohort of 6,398 women with a clinically documented ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
192
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(211 citation statements)
references
References 34 publications
6
192
0
6
Order By: Relevance
“…Endometriosis has been suggested to increase the risk of developing EOC (5). Compared to the serous surface epithelial subtype (serous adenocarcinoma, SAC), which comprises the majority of EOC, some types such as CCC and endometrioid adenocarcinoma (EAC) have been associated with endometriosis (6).…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis has been suggested to increase the risk of developing EOC (5). Compared to the serous surface epithelial subtype (serous adenocarcinoma, SAC), which comprises the majority of EOC, some types such as CCC and endometrioid adenocarcinoma (EAC) have been associated with endometriosis (6).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that women with ovarian endometriomas in this cohort had a ninefold increased risk to develop ovarian cancer. 3,4 As shown on the other hand by Vercellini et al 20 in 556 patients that underwent surgery for ovarian cancers, the frequency of simultaneous endometriosis was also significantly higher with 26.3, 21.1 and 22.2% in cases with endometrioid ovarian carcinomas, ovarian clear cell carcinomas or mixed subtypes, respectively, compared with 3.6-5.6% in serous, mucinous and miscellaneous ovarian cancers. In another study with 127 patients with primary ovarian carcinomas endometriosis rates of 70% were reported for ovarian clear cell carcinomas (30/43) and 43% for endometrioid ovarian carcinomas (3/7), whereas only 7% of the serous carcinomas (4/60) and none of the mucinous carcinomas (0/17) showed simultaneous endometriosis.…”
Section: Discussionmentioning
confidence: 79%
“…6 Several studies indicated that in women with ovarian endometriosis there is an increased risk for the development of epithelial ovarian cancer, especially the histological subtypes of ovarian clear cell carcinomas and endometrioid ovarian carcinomas. 4 4 reported 46 cases of ovarian carcinomas in a large prospective population-based Japanese study with an ovarian endometriosis cohort of 6398 women and a follow-up of up to 17 years. It was shown that women with ovarian endometriomas in this cohort had a ninefold increased risk to develop ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations